Effects of deposition speed and extrusion temperature on fusion between filaments in single-layer polymer films printed with FFF - Binghong Yin; Qinghao He; Lin Ye (Advanced Industrial and Engineering Polymer Research, 2021)
Fused filament fabrication (FFF) is an additive manufacturing technology in which a fused filament is deposited in a controlled manner over or adjoining previous deposited filaments, leading to construction of a structural part. This study aims to characterise the extent of fusion bonding between individual filaments using printed single-layer films, which helps understand the process–structure–property relationship, optimising process parameters (i.e. deposition speed and extrusion temperature) involved in the FFF process. For a brittle polylactic acid (PLA) and a ductile polypropylene (PP), single-layer double-edge notched tensile (DENT) specimens with sharp cracks parallel to the deposition direction was fabricated using FFF of different extrusion temperatures (from 200 °C to 260 °C) and deposition speeds (from 30 mm/s to 90 mm/s). The fracture toughness (Kc), defined as the critical stress intensity factor at the critical load for brittle fracture of PLA and the specific essential work of fracture (we), as an indicator of the fracture toughness for ductile fracture of PP, were characterised. The results demonstrate that this methodology proved to be an effective tool to identify the effects of process parameters on fusion bonding in the FFF process, showing the strong sensitivity of fracture toughness, either KC for PLA or we for PP, to the extent of fusion bonding between individual filaments.